LEGAL SAFEGUARDS FOR CITIZENS AFFECTED BY INTERNET FRAUD (VERITAS LEGIS JOURNAL, 2026)
The article examines the improvement of criminal procedure regulation in the Republic of Kazakhstan in the context of the growth of cybercrime and the development of international cooperation in this field. It analyses the key strategic documents in the sphere of cybersecurity (the Cybersecurity Concept “Cyber Shield of Kazakhstan” and the Concept for Digital Transformation, Development of ICT and Cybersecurity for 2023–2029), as well as the significance of Kazakhstan’s accession to the Budapest Convention on Cybercrime and the UN Convention on Cybercrime for facilitating cross-border access to electronic evidence and ensuring prompt international cooperation. The article argues that the current criminal procedure legislation provides only fragmentary regulation of electronic documents and computer information, which does not meet the practical needs of detecting and investigating cybercrimes. It substantiates the necessity of legally enshrining the concept of electronic evidence, its classification depending on the place of storage, and the introduction of special procedural mechanisms for obtaining, preserving, seizing and using such evidence in criminal proceedings, taking into account relevant international standards.
Keywords: cybercrime; information security offences; electronic evidence; criminal offences; ICT sector, internet fraud; criminal liability